Pulmonary asbestos bodies and asbestos fibers as indicators of exposure - Karjalainen, Antti; Nurminen, Markku; Vanhala, E.; Vainio, Harri; Anttila, S. (Scandinavian Journal of Work, Environment & Health, 1996)
' ' OBJECTIVES ': 'The aim of the study was to analyze the correlation between pulmonary concentrations of asbestos bodies and asbestos fibers and to characterize asbestos body counts from lung tissue of Finnish patients occupationally exposed and unexposed to asbestos.' ' METHODS ': 'Ninety-nine surgically treated lung cancer patients were investigated. The number of asbestos bodies in iron-stained 5-µm histological lung tissue sections was determined by optical microscopy, and the pulmonary concentration of asbestos fibers was assessed by scanning electron microscopy. The correlation between asbestos body and asbestos fiber counts was calculated with linear regression. The asbestos body and asbestos fiber concentrations were also compared with exposure history according to a personal interview of the patients.' ' RESULTS ': 'The average number of asbestos bodies ranged from
Keywords: anthophyllite; crocidolite; electron microscopy; optical microscopy